THU0117 Independent associations of disease characteristics and cardiovascular risk factors with left ventricular diastolic function in rheumatoid arthritis. (15th June 2017) - Millen, AM; Mokotedi, L; Gunter, S; Robinson, C; Norton, GR; Woodiwiss, AJ; Tsang, L; Dessein, PH
Abstract : Background: Heart failure contributes to the excess mortality experienced by patients with rheumatoid arthritis (RA) (1). Impaired diastolic function represents a pre-clinical cardiac alteration which is highly predictive of cardiac events and often progresses to heart failure. Diastolic dysfunction is the most common cause of heart failure in patients with a preserved ejection fraction. Whereas RA is associated with an increased prevalence of impaired diastolic function (2, 3), the pathophysiological mechanisms that mediate this comorbidity await further elucidation. Objectives: This study aimed to identify potential determinants of ventricular (LV) diastolic function in patients with RA. Methods: LV diastolic function was determined in 176 patients with RA; 9 patients had established cardiovascular disease. LV diastolic function was determined by echocardiography from the ratio of early-to-late transmitral blood flow velocity (E/A), the ratio of E to the mean of the lateral and septal wall myocardial tissue lengthening at the mitral annulus (e') (E/e'), and the lateral e'. Relationships of comprehensively evaluated traditional cardiovascular risk factors and RA characteristics with markers of LV diastolic function were determined in confounder adjusted multivariate regression models. Results: Disease duration (partial r=-0.23, p=0.00), rheumatoid factor status (partial r=-0.16, p=0.04) and erythrocyte sedimentation rate (partial r=-0.16, p=0.04) were associated with lower logarithmically transformed (log) E/A. Upon further adjustment for left ventricular mass index or relative wall thickness, these relationships remained significant (p≤0.05). Diastolic blood pressure was related to log E/e' (partial r=-0.16, p=0.04); this association was no longer significant after additional adjustment for left ventricular mass index (p=0.06) or relative wall thickness (p=0.06). Disease duration (partial r=-0.32, p=0.00), waist-to-hip ratio (partial r=-0.29, p=0.00) and triglycerides (partial r=-0.17, p=0.03) were related to log lateral e'. These relationships remained significant upon further adjustment for left ventricular mass index (for all p=0.00) or relative wall thickness (for all p=0.00). In sensitivity analysis among RA patients without established cardiovascular disease (n=167), the results were not materially altered. Conclusions: Modifiable traditional cardiovascular disease risk factor and disease characteristics are consistently associated left ventricular diastolic function in RA. References: Nicola PJ, Crowson CS, Maradit-Kremers H et al. Contribution of congestive heart failure and ischemic heart disease to excess mortality in rheumatoid arthritis. Arthritis Rheum 2006;54:60–7. Gonzalez-Juanatey C, Testa A, Garcia-Castelo A et al. Echocardiographic findings in long-term treated rheumatoid arthritis patients without clinically evident cardiovascular disease. Semin Arthritis Rheum 2004;33:231–8. Liang KP, Myasoedova E, Crowson CS et al. Increased prevalence of diastolic dysfunction in rheumatoid arthritis. Ann Rheum Dis 2010;69:1665–70. Disclosure of Interest: None declared